Participatory Evaluation as a Pedagogical Tool for Enhancing Student Agency in Community-Based Islamic Schools - Harahap, Friska Indria Nora; Kamil, Mustafa; Ardiwinata, Jajat S.; Sardin; Hamka, Ade (Jurnal al-Thullab, 2025)
This study is grounded in the need to shift educational evaluation from a teacher-centered approach toward a more student-centered and reflective process. In many non-formal Islamic educational settings, evaluation practices remain informal, unstructured, and focused on outcomes rather than learning processes, which limits students’ ability to develop independence and metacognitive awareness. Therefore, this study aims to examine the implementation of participatory evaluation as a pedagogical tool to enhance student agency in a community-based Islamic learning environment. This research employs a descriptive qualitative approach, using in-depth interviews, participant observation, and document analysis, with thematic analysis to interpret the data. The findings reveal that participatory evaluation, implemented through reflective journals and dialogic feedback, significantly enhances students’ metacognitive awareness, learning autonomy, and sense of responsibility. Evaluation is reconceptualized as assessment as learning, where students actively reflect on and regulate their own learning processes. The study contributes theoretically by integrating participatory evaluation with Islamic values, particularly muhasabah (self-reflection), and practically by offering an alternative evaluation model for strengthening independent and reflective learning in community-based Islamic education.